The multiple roles of the task design mediator in telecollaboration. Issue 3 (26th April 2017) - Fuchs, Carolin; Snyder, Bill; Tung, Bruce; Jung Han, Yu
Abstract: This case study explores how a Chinese-American novice teacher acted as mediator in a telecollaboration with student teacher (ST) peers in the USA who designed tasks for his English as a foreign language (EFL) learners in China. The novice teacher was instrumental in mediating the student teachers' task design process by providing feedback regarding technological and institutional constraints, and the nuances of his target student population. He appropriated and adapted the tasks to make them relevant for his EFL learners. Against the backdrop of the three dimensions of professional capital – human, social, and decisional – the research questions explored how the novice teacher used the different types of knowledge of context (pedagogical, institutional, technical) in relation to task design, and his perception of his role as mediator. Within a sociocultural framework for telecollaboration studies, this exploratory case study shares characteristics of ethnography, action research, and narrative inquiry. Data triangulation included text-based computer-mediated communication (CMC) data (Google Groups, emails), a narrative written by the novice teacher, and a semi-structured, reflective Skype interview with him. The findings indicate that he demonstrated high commitment, thorough preparation, continuous reflection, and development while navigating between his different roles of mediator, assessor, implementer, and field observer.